Willingness to obtain COVID-19 vaccination in adults with multiple sclerosis in the United States - Ehde, Dawn M.; Roberts, Michelle K.; Herring, Tracy E.; Alschuler, Kevin N. (Multiple sclerosis and related disorders, 2021)
•As COVID-19 vaccines become available, it is important to understand rates of vaccine acceptability in adults with multiple sclerosis (MS).•Two-thirds of the participants reported a willingness to obtain a COVID-19 vaccine, with education level, perceived risk for COVID-19, and trust in COVID-19 information sources positively associated with vaccine acceptability.•These findings have important implications for guiding vaccine uptake among vaccine eligible people with MS during the COVID-19 pandemic. Background: As vaccines for the coronavirus become available, it will be important to know the rate of COVID-19 vaccine acceptability in adults with multiple sclerosis (MS), given that vaccination will be a key strategy for preventing SARS-CoV-2 infections. Using a national sample of adults with MS in the United States obtained early in the COVID-19 pandemic, the current study aimed to: (1) assess willingness to get a COVID-19 vaccine when available; (2) determine demographic, MS, and psychosocial correlates of vaccine willingness; and (3) measure where people with MS get their COVID-19 information and their perceived trustworthiness of such sources, which may influence COVID-19 vaccine willingness. Methods: Adults with MS (N = 486) living in the United States completed a cross-sectional online survey (between 10 April 2020 and 06 May 2020) about their willingness to receive a COVID-19 vaccination once available. Participants also completed measures to describe the sample and to assess factors potentially related to vaccine willingness, including demographics, MS-specific variables, psychological measures, COVID-19 information sources, and perceived trustworthiness of their information sources. Results: Approximately two-thirds of the participants (66.0%) reported a willingness to obtain a future COVID-19 vaccine, whereas 15.4%of the sample was unwilling. Greater willingness to receive the vaccine was associated with having a higher level of education and holding a higher perception of one's risk of catching COVID-19. Participants reported accessing COVID-19 information from many different sources. Approximately a third (31.6%) of the sample reported getting their information from healthcare providers. Healthcare providers and the National MS Society had the highest perceived trustworthiness for COVID-19 information. The perceived trustworthiness of information sources was highly associated with vaccine willingness. Conclusion: Early in the pandemic, willingness to get a COVID-19 vaccine was not universal in this large sample or people living with MS. Vaccine willingness was associated with a few variables including education level, perceived risk for COVID-19 infection, and trust in COVID-19 information sources. These results have important implications for guiding healthcare providers and the MS community as COVID-19 vaccines become widely available.